Mārtiņa Lutera ietekme vācu valodā. Bībeles tulkojuma piemērs (Apustuļa Pāvila vēstule romiešiem) - Pencheva, Vasilena (Latvijas Universitāte, 2019)
Bakalaura darba nosaukums ir "Mārtiņa Lutera ietekme uz vācu valodu. Bībeles tulkojuma piemērs (Apustuļa Pāvila vēstule romiešiem)”. Bakalaura darbs ir veltīts valodas vēstures tēmai - vācu valodas attīstībai un uzsvērts tiek Mārtiņa Lutera Bībeles tulkojuma ieguldījumu tās attīstībā. Pētījuma mērķis ir noskaidrot, kā Lutera pēdējais Bībeles tulkojums un tā vēlākā 1984. gada versija atbilst principiem, kas formulēti Lutera "Atvērtajā vēstulē par tulkošanu". Lai sasniegtu šo mērķi, uzmanība pievērsta šādiem uzdevumiem: analizēt "Svētā Pāvila vēstuli romiešiem", balstoties uz 16. gadsimta Lutera bībeles tulkojumu, izpētīt Bībeles izdevuma vēsturi un salīdzināt 1545. gada "Sv. Pāvila vēstuli romiešiem" ar 1984. gada versiju. Pēc 1545. gada un 1984. gada bībeles izdevumu salīdzināšanas secināts, ka izmaiņas ir veiktas tikai teksta gramatiskajā līmenī, neskarot nozīmi, kura bija ļoti svarīga Mārtiņam Luteram. Nobeigumā ir secināts, ka Mārtiņa Lutera pēdējais Bībeles tulkojums un 1984. gada versija atbilst principiem, kas formulēti Lutera atklātajā vēstulē par tulkošanu.

The title of my bachelor thesis is: "Martin Luther's influence on the German language" and subtitles: "Examined by the example of the Bible translation (Letter of Saint Paul to the Romans)". My bachelor thesis is devoted to a language-historical topic, but rather the development of the German language, where I would like to emphasize the contribution of Martin Luther with his Bible translation. The purpose of my study is to examine how the last Bible translation by Luther and the later version from 1984 correspond to the principles formulated in Luther’s "Open Letter on Translating". In order to reach the goal, I concentrate on the following tasks: to analyze the "Letter of Saint Paul to the Romans" from 16th century Luther’s Bible translation, to examine the edition history of the Bible and to compare the "Letter of Saint Paul to the Romans" from 1545 and 1984. After the comparison of the fragment in the two versions of the Bible from 1545 and 1984, I found that changes in the 1984 Bible edition were available, but these changes only affected grammar, not the most important for Luther - the sense. As a conclusion, I can say that the last translation of the Bible by Luther himself and the later version of 1984 corresponds to the principles formulated in Luther's Open Letter on Translation.
Martin Luther`s influence on the german language. Examined by the example of the Bible translation (letter of St. Paul to the romans)
Keywords: Valodniecība; Luther; German; language; Bible; influence